2015
DOI: 10.1155/2015/659378
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Transglutaminase‐Regulated Transformed Growth Factor‐β1 in the Parasite Links Schistosoma japonicum Infection with Liver Fibrosis

Abstract: Transforming growth factor (TGF-β1) is among the strongest factors of liver fibrogenesis, but its association with Schistosoma-caused liver fibrosis is controversial. Tissue transglutaminase (tTG) is the principal enzyme controlling TGF-β1 maturation and contributes to Sj-infected liver fibrosis. Here we aim to explore the consistency between tTG and TGF-β1 and TGF-β1 source and its correlation with liver fibrosis after Sj-infection. TGF-β1 was upregulated at weeks 6 and 8 upon liver fibrosis induction. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
(62 reference statements)
3
13
0
Order By: Relevance
“…The expression of α-SMA, COL I, and COL III was moderate at week 8 after Sj infection (Figure 1 C, right ). Consistent with the results of our previous study ( 19 , 20 ), liver granuloma induced by Sj infection began at week 5, acute fibrosis began at week 6, and advanced liver fibrosis began at week 8. The areas of collagen deposition and the expressions of α-SMA, COL I, and COL III all decreased at week 12 (chronic liver fibrosis).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The expression of α-SMA, COL I, and COL III was moderate at week 8 after Sj infection (Figure 1 C, right ). Consistent with the results of our previous study ( 19 , 20 ), liver granuloma induced by Sj infection began at week 5, acute fibrosis began at week 6, and advanced liver fibrosis began at week 8. The areas of collagen deposition and the expressions of α-SMA, COL I, and COL III all decreased at week 12 (chronic liver fibrosis).…”
Section: Resultssupporting
confidence: 91%
“…Our previous work indicated that TGM2 contributes to liver fibrosis post Sj infection ( 19 , 20 ). Thus, both TGM2 and activation of the TLR4 signal pathway correlated with the development of liver fibrosis during Sj infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic Schistosoma infection is one of the known aetiologies leading to liver fibrosis. Schistosomiasis is a major neglected tropical infectious disease that has serious public health consequences (54). In China, schistosomiasis japonica is a major health risk for more than 50 million people (55).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, TGF-β drives TG2 expression, while TG2 contributes to the transcription, secretion and activation of TGF-β leading to the formation of an additional level of self-amplification loop in the pathogenesis of fibrosis. Not surprisingly, fibroproliferative diseases are characterized not only by enhanced TGF-β production, but also by enhanced TG2 expression [ 41 , 42 ]. The central role of TG2 in maintaining these diseases is proven by the observation that TG2 knock out mice are protected from fibrosis in several experimental fibrosis models [ 43 , 44 ].…”
Section: Transglutaminase 2 In Fibroproliferative Diseasesmentioning
confidence: 99%